VHF Doppler Radio Direction Finding Using an Eight-Element Switched Antenna Array - Arif Basuki; Denny Dermawan; Diah Suwarti Widyastuti; Bagas Nur Susanto; Adi Setiawan (Institut Teknologi Dirgantara Adisutjipto, 2026)
Communication between radio transmitters and receivers is commonly evaluated based on signal quality, while the direction of arrival (DoA) of the signal is less frequently exploited in conventional communication systems. This study presents the design and preliminary field validation of a Doppler-based Radio Direction Finder (RDF) operating in the Very High Frequency (VHF) band using an eight-element switched antenna array. The proposed system applies a single-receiver pseudo-Doppler architecture in which eight antenna elements are sequentially switched to emulate virtual antenna rotation and generate a Doppler-modulated audio-frequency signal. The signal is processed through filtering, zero-crossing detection, and phase-based bearing estimation, and the resulting direction is displayed using a 16-segment circular LED indicator with 22.5° angular resolution. Field measurements were conducted at three locations in the 144–146 MHz band, with transmitter–receiver distances ranging from approximately 100 m to 1,500 m. The measured angular errors were 4.455°, 7.551°, and 5.154°, corresponding to relative angular errors of 1.24%, 2.10%, and 1.43%, respectively, with an average relative angular error of approximately 1.59%. These results indicate that the proposed eight-element pseudo-Doppler RDF prototype can provide practical bearing estimation under the tested VHF field conditions. However, further experiments involving more azimuth angles, repeated measurements, and direct comparison with a four-element configuration are required to confirm robustness and quantify the performance improvement of the proposed system.